Jules Verne: from the Odyssey to Science Fiction (Castilla. Estudios de Literatura, 2018)
This article tries to remember the important role played by Jules Verne in modern fantastic literature. His Extraordinary Voyages modernizes the classic odyssey and, thanks to the incorporation of science and the importance it attaches to verisimilitude in the fantastic literature, creates science fiction, while creating a fantastic literature based not on terror, as was common in his time, but on fascination. Utopia is a very old genre but it does not happen the same to dystopia, which owes much to the writer of Nantes.
Keywords: Jules Verne; Modern Odyseey; Fntastic Literatura; Science Fiction; Dystopia